Key features and updates for Origin 2018 - James G. Moberly; Matthew T. Bernards; Kristopher V. Waynant (Journal of Cheminformatics, 2018)
Abstract OriginLab’s newest version update to Origin and OriginPro includes ease-of-use features, like Origin Central updates and creation of an App Center, as well as larger changes like the addition of Unicode characters, alteration to how user files are stored and visually searched, and user input formula in cells within worksheets. These features add additional value to an already powerful data analysis and plotting software package.